Acquisition of responding with a remifentanil-associated conditioned reinforcer in the rat - Bertz, Jeremiah W. (2013)
RATIONALE: Drug-associated environmental stimuli may serve as conditioned reinforcers to enhance drug self-administration behaviors in humans and laboratory animals. However, it can be difficult to distinguish experimentally the conditioned reinforcing effects of a stimulus from other behavioral processes that can change rates of responding. OBJECTIVES: To characterize the conditioned reinforcing effects of a stimulus paired with the μ-opioid agonist, remifentanil, using a new-response acquisition procedure in the rat. METHODS: First, in Pavlovian conditioning (PAV) sessions, rats received response-independent IV injections of remifentanil and presentations of a light-noise compound stimulus. In paired PAV groups, injections and stimulus presentations always co-occurred. In random PAV control groups, injections and stimulus presentations occurred with no consistent relationship. Second, in instrumental acquisition (ACQ) sessions, all animals could respond in an active nose-poke that produced the stimulus alone or in an inactive nose-poke that had no scheduled consequences. RESULTS: During ACQ, rats made significantly more active nose-pokes than inactive nose-pokes after paired PAV, but not after random PAV. Between groups, rats also made more active nose-pokes after paired PAV than after random PAV. After paired PAV, increased active responding was obtained under different schedules of reinforcement, persisted across multiple ACQ sessions, and depended on the number of PAV sessions conducted. CONCLUSIONS: The remifentanil-paired stimulus served as a conditioned reinforcer for nose-poking: responding depended on both the contingency between the stimulus and remifentanil and the contingency between the nose-poke and the stimulus. Generally, new-response acquisition procedures may provide valid, flexible models for studying opioid-based conditioned reinforcement.